2013
DOI: 10.1002/adma.201303287
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Engineered Microcapsules as Intracellular Anchors for Remote Control Over Cellular Mobility

Abstract: Living cells are anchored with magnetic microcapsules that allow in vitro manipulation via a magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…This result indicates that magnetic microcapsules made of poly(allyl)amine hydrochloride (PAH)/ poly(styrene) sulfonate (PSS) and Fe 3 O 4 nanoparticles have mild toxicity when the number of capsules per cell does not exceed 20. These observations are in a good agreement with earlier report, demonstrating that immortalized cell lines are more tolerant to high capsule concentrations than primary cell lines such as MSCs. Thus, we may conclude that the negative effect of microcapsules containing metal nanoparticles on cell viability is in favor to use such microcontainers for cell functionalization as vehicles to control cell behavior and migration.…”
Section: Resultssupporting
confidence: 93%
“…This result indicates that magnetic microcapsules made of poly(allyl)amine hydrochloride (PAH)/ poly(styrene) sulfonate (PSS) and Fe 3 O 4 nanoparticles have mild toxicity when the number of capsules per cell does not exceed 20. These observations are in a good agreement with earlier report, demonstrating that immortalized cell lines are more tolerant to high capsule concentrations than primary cell lines such as MSCs. Thus, we may conclude that the negative effect of microcapsules containing metal nanoparticles on cell viability is in favor to use such microcontainers for cell functionalization as vehicles to control cell behavior and migration.…”
Section: Resultssupporting
confidence: 93%
“…Super-paramagnetic iron oxide nanoparticles have been widely used in biomedical applications, such as clinical imaging, cell patterning, blood purification and vectoring delivery agents in the treatment of tumors by hyperthermia techniques [19][20][21][22][23][24]. Due to their innate magnetic characteristics and biocompatibility, iron oxide nanoparticles have been encapsulated in biomaterials to fabricate novel cell scaffolds [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Pavlov et al demonstrated an interesting strategy to use magnetic microcapsules for the magnetic guidance of live cells (Figure 2(d)) [12]. This strategy was based on the internalization of magnetically responsive capsules by cells (Figure 2(e,g)).…”
Section: Harnessing Multifunctional Hybrid Microcapsules In Cell Engimentioning
confidence: 99%